Primary School Supervision During the COVID-19 Pandemic: A Qualitative Study of How Elementary School Superintendent in Bontang City Responded to Growing Needs - Nurlaelah Nurlaelah; Anugrah Anugrah; Warman Warman (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Supervisors are parties who are expected to provide professional development for teachers in teaching and learning activities and provide the latest information related to educational policies, provide alternative solutions when schools have difficulty improving quality or running educational programs. However, limited attention is paid to primary school supervision issues during the current COVID-19 pandemic. This article discusses the implementation of primary school supervision in Bontang City during the COVID-19 pandemic. A qualitative approach with a descriptive method is used to describe the conditions that occurred at the time the research was conducted and then examine the causes of the conditions under study. Then, the researcher also explained how the supervisory plan for monitoring, implementing and evaluating Bontang City elementary schools during the Covid-19 pandemic. The results showed that school supervision during the pandemic was not carried out properly. The implementation of supervision does not follow the supervisor's technical instructions during the COVID-19 pandemic. As a result, the supervision process does not provide real implications for the implementation of effective learning.